ADAM10 modulates SOX9 expression via N1ICD during chondrogenesis at the cranial base. Issue 67 (14th November 2018) - Fu, Runqing; Wang, Xiaoting; Xia, Lunguo; Tan, Yu; Liu, Jiaqiang; Yuan, Lingjun; Yang, Zhi; Fang, Bing
Abstract : ADAM10 modulates SOX9 expression via Notch signaling pathway during chondrogenesis in cranial base. Abstract : The cranial base is the foundation of the craniofacial structure, and any interruption of the cranial base can lead to facial deformity. The cranial base develops from two synchondroses via endochondral ossification. Chondrogenesis is an important step in endochondral ossification. A disintegrin and metalloprotease (ADAM) 10 participates in the Notch1 signalling pathway, which has been reported to regulate chondrogenesis via a SOX9-dependent mechanism. However, little is known about the function of ADAM10 in chondrogenesis. In this study, adam10-conditional-knockout (cKO) mice exhibited sharper naso-labial angles and flatter skulls than wild-type (WT) mice. In the sagittal plane, SOX9 was more widespread in the cranial base in Adam10-cKO mice than in WT mice. For in vitro experiments, we used the ATDC5 cell line as a model to investigate the role of ADAM10 in chondrogenesis. Plasmid 129 was designed to decrease the expression of Adam10; the resulting downregulation of Adam10 reduced the production of N1ICD. Plasmid 129 increased the expression of SOX9 under chondrogenic induction, and this increase could be inhibited by transfection with exogenous N1ICD. Collectively, these results show that ADAM10 participates in chondrogenesis by negatively regulating SOX9 expression in an N1ICD-dependent manner during cranial base development.